Source apportionment of polycyclic aromatic hydrocarbons and black carbon at the western coastal areas of the Yellow Sea based on isotopic signatures - Yipeng Wang (Elsevier, 2021)
The stable and radioactive isotopes (δ13C, Δ14C and δ2H) of black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) in the sediment from the western coastal areas of the Yellow Sea (i.e. the Jiangsu coastal areas (JCA)) were examined to identify the sources these environmental pollutants in the JCA. The results presented that the spatial heterogeneous characteristics of BC and PAHs were markedly presented in the JCA. This was suggestive of presence of the contributions of multiple potential environmental pollution sources. This can be solved and decoupled by applying the Bayesian mode. Accordingly, the statistical model showed that the major environmental pollution contributions is considered as coal combustion (39%) in the JCA. The liquid fossil fuels, petrogenic sources, and biomass combustion were accounted for 27%, 19%, and 15% in the JCA, respectively. The stable and radioactive carbon isotopic ratios (δ13C and Δ14C) of BC collected from the JCA are also applied to discriminate quantitatively the source of contamination. It is demonstrated that the BC in this study originates mainly from combustion of fossil fuels. And rock-derived BC as well as C3 and C4 plants combustions are also numerically predominant for BC and PAHs pollution in the coastal area. It is implied that the environmental PAHs and BC in the JCA seem to origin relatively homologies sources. Furthermore, it is suggested that the stable and radioactive carbon isotopes as well as hydrogen isotopes may be powerful and useful method to source apportionment, and have much advantages to clarify quantitatively BC and PAH pollutions in the coastal environment, but also detailed insights into the source apportionment and fate of the organic carbon in the marginal sea.